Supported Lipid Bilayers of Escherichia coli Extracted Lipids and Their Calcium Dependence - Kakimoto, Yasuhiro; Tero, Ryugo (Frontiers in Materials, 2018)
Formation of supported lipid bilayer (SLB) and additional structures of Escherichia coli (E. coli) lipids were investigated with fluorescence microscopy and atomic force microscopy. Ca2+ in the aqueous phase with concentration above 2 mM was necessary for the formation of SLB. Additional lipid structures, string-like structures, the second lipid bilayer, and multilayer stacking appeared on the first layer SLB depending on Ca2+ concentration. The bridging effect of Ca2+ between the negatively charged E. coli lipid bilayers and substrate is the dominant factor determining the two-dimensional and three-dimensional morphology of the E. coli lipid bilayer membranes.